2015
DOI: 10.1007/s12035-015-9467-9
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam Prevents Perforin Mediated Neuronal Injury Induced by Acute Cerebral Ischemia Reperfusion

Abstract: The purpose of this study is to explore the neuroprotection mechanism of levetiracetam (LEV) with acute focal cerebral ischemia-reperfusion (I/P) mouse. The cerebral artery I/P animal model was prepared with a middle artery cerebral occlusion method. For drug intervention, mice were intraperitoneally injected with LEV with a dose of either 15 or 150 mg/kg. Neuronal injury was evaluated by measuring the infarct area, apoptosis ratio, and observation of blood-brain barrier ultrastructure with transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 52 publications
1
12
1
Order By: Relevance
“…23 Our results showed that MCAO caused an increase in the infarct size as compared with the sham group, the histopathological examination revealed edema, increase in the cellular permeability as well as infiltration of inflammatory cells. We found that LEV treatment caused significant decrease in infarction volume as reported by Cuomo et al 27 and Zhang et al 25 LEV improved memory and learning in the LEV-treated group compared with the I/R group. 24 The results of the current study also showed impairment in memory and learning function in the ischemic group as compared with the sham-operated group as reported earlier.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…23 Our results showed that MCAO caused an increase in the infarct size as compared with the sham group, the histopathological examination revealed edema, increase in the cellular permeability as well as infiltration of inflammatory cells. We found that LEV treatment caused significant decrease in infarction volume as reported by Cuomo et al 27 and Zhang et al 25 LEV improved memory and learning in the LEV-treated group compared with the I/R group. 24 The results of the current study also showed impairment in memory and learning function in the ischemic group as compared with the sham-operated group as reported earlier.…”
Section: Discussionsupporting
confidence: 84%
“…Global ischemia is produced by transient bilateral carotid artery stenosis, while focal ischemia is produced by transient MCAO. 25 F I G U R E 3 A, Photomicrograph of the cerebral cortex of control group showing evenly distributed variable sized neuronal cells surrounded by eosinophilic neurofibrillary material, which contains normal glial cells: astrocytes and oligodendrocytes (H&E ×400). 23 Our results showed that MCAO caused an increase in the infarct size as compared with the sham group, the histopathological examination revealed edema, increase in the cellular permeability as well as infiltration of inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16] Pfn is a cytolytic protein that, on release, inserts itself into the plasma membrane of the target cell, forming a pore that leads to necrotic cell death because of loss of plasma membrane homeostasis with excessive uptakes of water and loss of intracellular contents. Recent studies showed the significant role of direct cytotoxicity through perforin (Pfn) in CD8 + T cell-mediated neuronal damage during ischemia.…”
Section: Introductionmentioning
confidence: 99%